2003
DOI: 10.1068/p5098
|View full text |Cite
|
Sign up to set email alerts
|

An Encoding Advantage for Own-Race versus Other-Race Faces

Abstract: Studies have shown that individuals are better able to recognise the faces of people from their own race than the faces of people from other races. Although the so-called own-race effect has been generally regarded as an advantage in recognition memory, differences in the processing of the own-race versus other-race faces might also be found at the earlier stages of perceptual encoding. In this study, the perceptual basis of the own-race effect was investigated by generating a continuum of images by morphing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
128
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(143 citation statements)
references
References 24 publications
14
128
0
Order By: Relevance
“…These effects are consistent with past researcher's suggestions that the N200 reflects individuation and deeper processing when viewing faces, which we would expect to be greater for faces of Whites (because they are members of a culturally powerful group and/or the ingroup) and faces displaying happy, approachable expressions Ito & Urland, 2003;James et al, 2001;Tanaka et al, 2004;Walker & Tanaka, 2003).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These effects are consistent with past researcher's suggestions that the N200 reflects individuation and deeper processing when viewing faces, which we would expect to be greater for faces of Whites (because they are members of a culturally powerful group and/or the ingroup) and faces displaying happy, approachable expressions Ito & Urland, 2003;James et al, 2001;Tanaka et al, 2004;Walker & Tanaka, 2003).…”
Section: Discussionsupporting
confidence: 91%
“…The sagittal main effect (F(2,56)=36.43, p<.01) showed that the N100 was maximal at Cz (M=−6.20 μV) as compared with the average of Fz (−4.92 μV) and Pz (M=−3.30 μV, F(1,28)=94.60, p<.01). The Race × Sagittal interaction (F (2,56)=4.91, p<.05) showed that N100 amplitudes were larger to Blacks than Whites at Cz (M Black =−6.40 μV and M White =−6.00 μV , F(1,28) 2003; James et al, 2001;Tanaka et al, 2004;Walker & Tanaka, 2003). Like the P200, there was no evidence of an interaction between race and emotion in the N200.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…It is possible that unconsciously they could sculpt the face from a limited memory database especially when partially trained; Secondly, the facial recognition ability of the assessors utilised for accuracy assessment may be affected by unfamiliarity with the ancestry of the reconstructed face. Even though psychological research into the CRE has primarily been in memory recall rather than comparison without memory load, the CRE has also been observed in performances with minimal required memory [79] and in the early stage of perceptual encoding face process [68,80]. These studies suggest that there is a possibility that the CRE may affect the accuracy of recognising or identifying CFRs by assessors from another ancestry to the reconstructed face.…”
Section: Introductionmentioning
confidence: 98%
“…Other image-manipulation techniques allow us to alter images in ways which we predict will affect judgements of gender, age, race or any number of other psychologically relevant dimensions (e.g. Busey, 1998;Oosterhof & Todorov, 2008;Stewart et al, 2012;Walker & Tanaka, 2003). In short, the facility to manipulate images in wellspecified ways opens up the opportunity to design perceptual experiments which were impossible in the era before widely-available graphical computers.…”
Section: Introductionmentioning
confidence: 99%